Indonesian Islamic Comercial Banks Profitability: Role of Murabahah Financing, Musyarakah Financing, NPF, and BOPO - Siti Adifatun Amanah; Suryani Sri Lestari; Atif Windawati (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2023)
This study to analyze the significance of the effect of Murabahah Financing, Musyarakah Financing, Non-Performing Financing (NPF), and Operating Expenses on Operating Income (BOPO) on Profitability at Islamic Commercial Banks in Indonesia for the 2018-2022 period. We employ 6 (six) Islamic Commercial Banks in Indonesia for the 2018-2022 period, which were selected using Purposive Sampling technique. The analysis model used in this research is the Multiple Linear Regression Analysis Model processed with the SPSS 26.00 program. The results of hypothesis proving and discussion show that the effect of Murabahah Financing, Musyarakah Financing, Non-Performing Financing (NPF), and Operating Expenses on Operating Income (BOPO) simultaneously has a significant effect on Return on Asset (ROA). Partially, the Murabahah Financing ratio has a positive and significant effect, Musyarakah Financing has a negative but significant effect, the Non-Performing Financing (NPF) ratio has a negative but insignificant effect, and Operating Expenses on Operating Income (BOPO) has a negative and significant effect on ROA at Islamic Commercial Banks in Indonesia for the period 2018- 2022.